Phase composition and dielectric properties of spark plasma sintered PbZr0.52Ti0.48O3 - Abhishek Kumar Gupta; Anjan Sil (Materials Research Express, 2020)
In the present work, lead zirconate titanate PbZr _0.52 Ti _0.48 O _3 (PZT) bulk ceramic powders having composition aimed for morphotropic phase boundary (MPB) were synthesized by conventional solid-state reaction and sintered by novel spark plasma sintering (SPS) method. The samples sintered at four different temperatures of 800, 850, 900 and 950 °C are found to have almost same density. The effect of SPS temperature on microstructure, phase constituents and dielectric properties is investigated. Rietveld refinement of XRD patterns of samples was carried out to estimate the phase composition revealing that the enhanced dielectric response is due to the presence of monoclinic phase along with the tetragonal phase in the synthesized material. The maximum room temperature dielectric constant ε _r ∼950 was found for the sample sintered at 900 °C. It is observed that the temperature has a significant role in resulting change of phase composition and dielectric performance of all the samples due to sublimation of PbO content.